Factors Leading to Voluntary Labour Turnover of Accountants in Microfinance Institutions: A Case Study of Kenya Women Finance Trust (KWFT) - Mwaniki, Daniel (My University, 2011)
Kenya Women Finance Trust for the past years has been suffering from a high level of accountant’s turnover. This high turnover rate can lead to substantial negative consequences for the institution. Besides the costs associated with actual separation of the employees and recruiting, hiring and training of new staff, other costs may not be easily measured. The analysis ofthe number of leavers and the reason why they leave provides information that will indicate whether any action is required to improve retention rates. It can prompt further investigations to establish underlying causes and identify remedies. The study will be of benefit to management of KWFT in understanding the reasons for high Accountants labour turnover and take remedial measures amend certain policies that contribute to high labour turnover which will lead to better service to the clients. The sample of Accountants was selected from a population of all Accountants currently working at KWFT, former Accountants and all the 14 Regional Accountants working in the organization. Proportional sampling method was used to select the sample of current and former accountants to be studied. This ensured that all regions of KWFT were fairly represented in the study. The regions were treated as sub- population frames from where the sample to be studied was selected. Questionnaires were used to collect data for this study. This is because the questionnaire enabled the researcher to get first hand information about the work situation. The data provided in summaries the target population. The data was then presented in graphical formats and percentage terms in tabular format. The study shows that the salary paid to accountants did not match that of competition. The officers also indicated that they would prefer an output based reward system. The majority of those who have left employment or have thought of leaving cite pay as one of the major reasons. In addition the current and former Accountants felt that pay level did not match up well to the workload in KWFT. The study also revealed that the current and former Accountants plus the Regional Accountants felt that training in KWFT is very good and well handled. The study showed that the Accountants did not think they got adequate opportunity for personal development, advancement and promotion opportunities. The managers felt it was adequate. Majority of respondents from the three groups indicated that career development was one of the major causes of labour Accountants’ turnover. The majority of the former and present Accountants were also dissatisfied in working long hours. Only a minority of the Accountants cited relationship with supervisor as a reason of leaving or thinking of leaving KWFT employment. One of the recommendations is to introduce an output based reward system for the Accountants and match demand for high performance with equally competitive pay package. In addition, avoid benchmarking competitors pay levels because the Accountant feel KWFT demands more output than its competitors. It will also be necessary to develop a policy for Accountants’ career development with a clear career path that is properly defined, communicated and followed. KWFT should also address the Accountants’ appraisal system to ensure fairness in promotion. A policy for further education should be developed by either organizing staff to take study leave or giving them financial support to minimize the number of accountants resigning to seek further education. Kenya Women Finance Trust should employ adequate Accountants to cope with the challenges that make the staff work for long hours. Also the need to computerize most of the processes would save on time spent in the office by the accountants. The Accountants’ workload should also be addressed by finding out whether they consider it high and relative to rewards they get. Trainings to equip managers with necessary supervisory skills should be conducted regularly. KWFT should also conduct regular salary surveys within the microfinance industry.